Retorika v poslovnem komuniciranju: delovni listi - Potočnik Topler, Jasna; Strašek Dodig, Mojca (2018)
Rhetoric in Business: Worksheets . Rhetoric is the art of persuasion. For thousands of years, people have praised and studied it. However, the foundations of rhetorical theory were laid by the Ancient Greek Philosopher Aristotle. Throughout history, rhetoric experienced development, ascents, as well as falls. Today, we are increasingly aware of the significance of mastering this skill in a wide variety of areas, since it contributes to better reading literacy of the individual and society as a whole. One of the goals of teaching rhetoric at the faculty is to prepare the students for analysis, and more precise and accurate formulation of arguments and persuasive techniques in their everyday lives: From private conversations, through media, study situations, and the writing of professional texts. It is also intended to acquaint students with various discourses, to teach them independent, self-confident, clear, structured and critical expression of their opinions, and the formation of well structured shorter and longer texts. The booklet contains worksheets for tourism students of academic study programme that are meant as a guide to introducing rhetoric for business communication, with topics such as history, genres, canons, persuasion and language at the forefront. Among other things, attention will be paid to the legal aspects of communication.
Keywords: rhetoric; business communication; persuasion; speech; performance